Microwave workshop for Windows - Colin White (Association for Learning Technology, 1995)
A suite of three programs has been developed to support the teaching of microwave theory and design. A secondary function of the package is to support microwave engineers by providing a library of utilities to assist their design function. All three programs were written in Visual Basic and are aimed at supporting both tutor-directed and student-centred learning methodologies. The development team consisted of three final-year degree students.